Who do you think you are? : three crucial conversations for coaching teens to college and career success - Smith, Stephen M., 1970-; Fanning, Shaun (John Wiley & Sons, Inc., 2017)
Give your kids their greatest chance at success Who Do You Think You Are''helps parents, school counselors, and administrators get teens thinking about'and interested in'their future careers. Success in college and beyond relies on thorough prior preparation; by identifying interests and passions early on, young people are better able to plan for the career they want by mapping out the academic path to support it. This book shows you how to guide teens along on this journey, and how to stick with them until they reach the goals they've set. From helping them discover just what it is they're interested in, to finding the institution that will help them flourish and setting out a clear "plan of attack," this book provides invaluable insight from an expert in student success.' No one expects every student to have a definitive life plan by high school graduation, but having'some idea of direction is critical. Nearly 3.3 million students will graduate high school this year, and most will head straight to college'but just 20 percent of those who pursue an associate's degree complete within four years, and only 60 percent of those who pursue a bachelor's degree complete within six years. Even those who earn a degree may struggle to move from school to work. Those who'do'succeed have done so because they've planned their work and worked their plans. This book shows you how to help your child to be one of the success stories.' -Map out an academic plan to support each kid's field of interest -Identify the best-fit institution to get them where they want to be -Balance support and independence throughout your teen's journey -Help your child be prepared for college so they can succeed far beyond ' Adults know that success in life comes from plenty of hard work and thorough preparation'but for kids in middle and high school, that lesson is just now beginning to hit home.'Who Do You Think You Are''helps you guide them through the transition successfully, so they can come out the other side exactly where they want to be.